Cultural capital at its best: factors influencing consumption of American television programmes among young Croatians. Issue 2 (2nd July 2016) - Pjesivac, Ivanka; Imre, Iveta
ABSTRACT: This study examined factors that influence the consumption of American television programmes among young Croatians, by conducting a paper and pencil survey ( N = 487). The results indicate that young Croatians are avid consumers of American dramas and sitcoms, and that a set of cultural capital variables is a significant predictor of the consumption of American TV. Knowledge of English language, of US lifestyle, consumption of American movies and American press all had a significant unique contribution to the model.